Stereometric and scaling law analysis of surface morphology of stainless steel type AISI 304 coated with Mn: a conventional and fractal evaluation - Shakoury, Reza; Grayeli Korpi, Alireza; Ghosh, Koushik; lu, tefan; Rezaee, Sahar; Mwema, Fredrick; Mardani, Mohsen; Arman, Ali (Materials research express, 2019)
The purpose of this study is to determine the micromorphology of stainless steel type AISI 304 coated with thin films of Manganese post-annealed by the flow of nitrogen at different annealing temperatures using atomic force microscopy (AFM) and fractal/multifractal analyses. The coated samples were annealed with a nitrogen flow of 400 sccm at four different temperatures of I group, 473 K; II group, 623 K; III group, 773 K; and IV group, 923 K. AFM was used to image the 3D surface micromorphology in tapping mode, on square areas of 2 × 2 m2. The approaches in both measurement and data analysis when using AFM analysis and surface fractal/multifractal analyses are essential for the correct interpretation of 3D surface topographic features and offer the 3D surface texture parameters and surface fractal dimension. The more irregular surface (Sq = 22.23 nm) was found in IV group, and the more regular surface (Sq = 5.86 nm) was found in II group. The result shows the effect of annealing treatment on fractal/multifractal characteristics of surfaces.